The Effect of Traditional Umbilical Cord Care on Cleanliness and Duration of Umbilical Cord Removal in Newborns - Yovita Luisa Onibala; Rani Safitri (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
Umbilical cord care is an important part of newborn care because the umbilical cord that has not fallen off has the potential to become an entry point for germs if not cared for hygienically. In the community, traditional umbilical cord care practices are still widely practiced and often do not comply with medical standards. This study aims to determine the effect of umbilical cord care education on cleanliness and duration of umbilical cord detachment in newborns in the Bongo 2 Community Health Center, Boalemo Regency. This study used a pre-experimental design with a one-group pretest-posttest approach. The study sample consisted of 24 newborns selected using a total sampling technique. The intervention in the form of umbilical cord care education was given to the parents of the babies, then measurements were taken of umbilical cord cleanliness and duration of umbilical cord detachment before and after education. Data analysis was performed using a paired t-test or Wilcoxon signed-rank test with a significance level of p < 0.05. The results showed an increase in umbilical cord cleanliness after education, with a p value = 0.001. In addition, the average duration of umbilical cord detachment decreased significantly after education, with a p value = 0.000. This study concludes that umbilical cord care education has a significant effect on improving hygiene and optimizing the duration of umbilical cord removal in newborns.